Liberalni pogled na ideološko in politično razhajanje s katoliško stranjo od ustanovitve Katoliškega političnega društva leta 1890 do ustanovitve Slovenskega društva leta 1891 v Ljubljani - Perovšek, Jurij (Prispevki za novejšo zgodovino, 2023)
After the end of the concord in Slovenian politics, in the time between the founding of the Catholic Political Society in 1890 and the liberal Slovenian Society in 1891 in Ljubljana, both ideological and political sides emphasized their fundamental views and views on the development of their mutual relations. The Catholic side has made it clear that it rejects liberalism and demands the consistent implementation of Christian principles in private and public life, and in the school field a religious school on a national basis. Liberalna drew attention to the problem of the political dominance of the clergy, towards which, in her opinion, they were tending in Carniola. She emphasized that the Church does not belong to interfere in politics, otherwise it can expect a response at the political level. In religious matters, liberals recognized the authority of church leaders, but in the field of education, they believed that the demands for a religious school were not justified, because it was already provided by the existing education system. The point of divergence between the two sides was the question of which principles – Catholic or liberal – should be the foundation of the nation's life. With a view to further social and political development, the strengthening of their ideological identity and its political establishment in the struggle for power that took place among the Slovenes in Carniola, they expressed their views more strongly on the liberal side, even with battle cries. For her, her ideological understanding of her Catholic opponent was authoritative.
Keywords: Anton Mahnič; dekliška šola; Ivan Šusteršič; Ivan Tavčar; Katoliško politično društvo; kranjski prepir; liberalizem; politični katolicizem; slogaštvo; Slovensko društvo; višja